Sodium Influx and Potassium Efflux Currents in Sunflower Root Cells Under High Salinity - Hryvusevich, Palina; Navaselsky, Ilya; Talkachova, Yuliya; Straltsova, Darya; Keisham, Monika; Viatoshkin, Aliaksei; Samokhina, Veranika; Smolich, Igor; Sokolik, Anatoliy; Huang, Xin; Yu, Min; Bhatla, Satish Chander; et al. (Frontiers in Plant Science, 2021)
Helianthus annuus L. is important oilseed crop, which exhibits moderate salt tolerance and can be cultivated in areas affected by salinity. Using patch-clamp electrophysiology, we have characterised Na+ influx and K+ efflux conductances in protoplasts of salt-tolerant Helianthus annuus L. hybrid KBSH-53 under high salinity. This work demonstrates that the plasma membrane of sunflower root cells has a classic set of ionic conductances dominated by K+ outwardly rectifying channels (KORs) and non-selective cation channels (NSCCs). KORs in sunflower show extreme Na+ sensitivity at high extracellular [Ca2+] that can potentially have a positive adaptive effect under salt stress (decreasing K+ loss). Na+ influx currents in sunflower roots demonstrate voltage-independent activation, lack time-dependent component and are sensitive to Gd3+. Sunflower Na+-permeable NSCCs mediate a much weaker Na+ influx currents on the background of physiological levels of Ca2+ as compared to other species. This suggests that sunflower NSCCs have greater Ca2+ sensitivity. The responses of Na+ influx to Ca2+ correlates well with protection of sunflower growth by external Ca2+ in seedlings treated with NaCl. It can be, thus, hypothesized that NaCl tolerance in sunflower seedling roots is programmed at the ion channel level via their sensitivity to Ca2+ and Na+.